ANALYSIS OF THE WORKS OF JADID LITERATURE IN THE RESEARCH OF INGEBORG BALDAUF - Sadullayeva Dilnoza Nortoji's daughter Base doctoral student of the National University of Uzbekistan named after Mirzo Ulugbek (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
In this article I. Baldauf's research on Uzbek jadid literature was analyzed. In particular, the analysis of the works of Fitrat was considered from the point of view of the scientist. It was noted that Baldauf was able to analyze the works by reading them fluently in the Uzbek language, as well as the connection he had established with Uzbek writers and readers. Records have been cited that Ingeborg Baldauf translated Fitrat's works into German and published them with commentaries.